Potential functional applications of extracellular vesicles: a report by the NIH Common Fund Extracellular RNA Communication Consortium. Issue 1 (28th August 2015) - Quesenberry, Peter J.; Aliotta, Jason; Camussi, Giovanni; Abdel‐Mageed, Asim B.; Wen, Sicheng; Goldberg, Laura; Zhang, Huang‐Ge; Tetta, Ciro; Franklin, Jeffrey; Coffey, Robert J.; Danielson, Kirsty; Subramanya, Vinita; et al.
Abstract : The NIH Extracellular RNA Communication Program's initiative on clinical utility of extracellular RNAs and therapeutic agents and developing scalable technologies is reviewed here. Background information and details of the projects are presented. The work has focused on modulation of target cell fate by extracellular vesicles (EVs) and RNA. Work on plant‐derived vesicles is of intense interest, and non‐mammalian sources of vesicles may represent a very promising source for different therapeutic approaches. Retro‐viral‐like particles are intriguing. Clearly, EVs share pathways with the assembly machinery of several other viruses, including human endogenous retrovirals (HERVs), and this convergence may explain the observation of viral‐like particles containing viral proteins and nucleic acid in EVs. Dramatic effect on regeneration of damaged bone marrow, renal, pulmonary and cardiovascular tissue is demonstrated and discussed. These studies show restoration of injured cell function and the importance of heterogeneity of different vesicle populations. The potential for neural regeneration is explored, and the capacity to promote and reverse neoplasia by EV exposure is described. The tremendous clinical potential of EVs underlies many of these projects, and the importance of regulatory issues and the necessity of general manufacturing production (GMP) studies for eventual clinical trials are emphasized. Clinical trials are already being pursued and should expand dramatically in the near future.